A Review of the Synthetic Account of 3-Methyl Pyrazolone as Anti-Inflammatory Agent - Nandkumar, Chitnis Akshata; Mahadev, Jadhav Kiran; Vishweshvar, Khandare Aishwarya; Salve, P. L.; Pise, V. J. (Asian Journal of Pharmaceutical Research and Development, 2024)
Pyrazolone is a five-membered lactam ring containing two nitrogens and one ketonic group in its structure. Numerous pyrazolone derivatives were exhibited with diverse biological, pharmacological, and chemical applications. The chemistry of pyrazolone has gained increasing attention due to its diverse pharmacological properties such as anticancer, analgesic, anti-inflammatory, antimicrobial, antioxidant, antifungal, antiviral, antidiabetic, and several other biological activities. Thus, because of their importance, synthetic strategies for existing as well as novel pyrazolone derivatives have been developed and explored their biochemical utility. Medicinal chemistry researchers have synthesized drug-like pyrazolone candidates with several medicinal features. This review paper intends to collect the references and comprehensively summarize the biological activity and the synthetic account of 3-methyl pyrazolone as an anti-inflammatory agent.